Effects of mechanical stresses on sperm function and fertilization rate in mice. (3rd March 2016) - Shi, Xiao; Wang, Ting; Qiu, Zhuo Lin; Li, Ke; Li, Liu; Chan, Carol Pui Shan; Chan, Si Mei; Li, Tian-Chiu; Quan, Song
ABSTRACT: In this study, we investigated whether any of the observed changes in mouse sperm function tests secondary to mechanical stresses (centrifugation and pipetting) correlate with sperm fertilization ability. Chinese Kunming mice were used as sperm and oocyte donors. Sperm samples were allocated evenly into centrifugation, pipette, and control groups. Sperm plasma membrane integrity (PMI), mitochondrial membrane permeability (MMP), baseline and stimulated intracellular ROS, and sperm fertilization ability were measured by hypo-osmotic swelling, flow cytometry, and fertilization tests. Parallel studies were conducted and all tests were repeated six times. Our results showed that after centrifugation, the progressive motility, average path velocity, and overall sperm motility and PMI decreased significantly ( p < 0.05). In addition, the MMP level decreased significantly in viable sperm when the centrifugation condition reached 1, 400 g × 15 minutes ( p < 0.05). When pipetting was performed two or more times, progressive motility, average path velocity, and overall sperm motility decreased significantly ( p < 0.05); when it was performed four or more times, sperm membrane integrity and intracellular basal ROS level of viable sperm was also significantly decreased ( p < 0.05). In conclusion, various mechanical stresses seem to affect sperm function, however this does not appear to alter fertilization rate. Laboratory handling steps should be minimized to avoid unnecessary mechanical stresses being applied to sperm samples.